Length-weight relationship, condition factor, and reproductive aspects of Lutke's halfbeak Hemiramphus lutkei (Valenciennes, 1847) from Seram Sea, Maluku, Indonesia - MATHEOS TALAKUA; SUADI SUADI; DJUMANTO DJUMANTO; EKO SETYOBUDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Talakua M, Suadi, Djumanto, Setyobudi E. 2023. Length-weight relationship, condition factor, and reproductive aspects of Lutke's halfbeak Hemiramphus lutkei (Valenciennes, 1847) from Seram Sea, Maluku, Indonesia. Biodiversitas 24: 6574-6583. Lutke's halfbeak is one of the Seram Sea's most commercially important fish species, providing food resources and community livelihood for an extended duration. Data and information on fish biology are important for responsible fisheries management. This research aimed to determine Luke's halfbeak's length-weight relationship, condition factor, and reproductive aspects at Seram Sea, Maluku. Fish samples were collected monthly for seven months, from August 2021 to February 2022. Each sample was measured for its length and weight and then dissected for sex and gonad maturity stage determination. The data was analyzed to determine the length-weight relationship, the condition factor, the distribution of gonadal maturity stage, and fecundity. Hemiramphus lutkei (Valenciennes, 1847), originating from the Seram Sea, indicates a negative allometric growth pattern. The average relative condition factor (Kn) of H. lutkei in the Maluku Seram Sea was around 1 and did not show a significant difference between males and females. The condition factor varied during the observation period, ranging from 0.92 to 1.09. The fish are mostly (80%) in good or very good condition. H. lutkei has a high potential fecundity; spawning was predicted throughout the year, with individual fecundity ranging from 263 to 1893 eggs. Luke's halfbeak populations in the Seram Sea could be exploited sustainably; however, this should be conducted with proper management.